DIVERSITY OF MOLLUSCA FILUM IN MEURAXA DISTRICT BANDA ACEH CITY AS A REFERENCE FOR INVERTEBRATED ZOOLOGICAL COURSES - Pertiwi, Rini; Aini, Qurratu; Hanum, Ulia; Suwarniati, Suwarniati (Prodi Tadris Biologi Fakultas Agama Islam Universitas Muhammadiyah Aceh, 2021)
This study aims to determine the types of animals from the mollusca phylum, habitat and to make the types of animals from the mollusca phylum as references in the Invertebrate Zoology course which is designed in the form of a pocket book. This research was started from April to June 2016, sampling of the phylum Mollusca was carried out in the Meuraxa District area of Banda Aceh city. In this study, sampling was carried out using the plot method and transect method in three predetermined observation areas. The first observation area is in the village of Alue Deah Tengoeh, the second area is in the village of Cot Lamkuweuh, and the third area is in the village of Lamjabat. Data analysis was carried out by describing each type of animal found in the Mollusca phylum. Furthemore, to determine the level of diversity of animal species from Mollusca phylum found in Meuraxa District, Banda Aceh city, the Shannon Wiener (H) diversity index was used. The results showed that the types of animals from the Mollusca phylum were 276 individuals consisting of 2 classes, 8 ordo and 11 families with 16 spesies. The results of the analysis of the diversity index shaw the value of H = 1.601, which means that the diversity level of Mollusca phylum in the Meuraxa District, Banda Aceh City is moderate, with an evenness index of E = 0.5 which means that the distribution of each type of animal from Mullusca phylum in each research area is relatively evenly distributed.